DIVERSITY OF SMALL MAMMAL IN THREE DIFFERENT HABITAT AT LHOKSEUMAWE ACEH PROVINCE - Nasir, Muhd; Amira, Yuli; Mahmud, Abdul Hadi (Journal of BioLeuser, 2016)
The study of small mammals diversity in three different habitat in Lhokseumawe Aceh province has been conducted. The three locations are the plantation, the bush, and riparian areas. Samples was collected by using 45 local traps. 40 samples have been colected consist of seven species. The recorded species are Bandikota bengalensis (Lesser Bandicoot Rat), Mus Caroli (Ricefield Mouse), Mus castaneus (Southeastern Asian house mouse), Rattus exulans (Polynesian rat), Rattus rattus (House rat), Rattus tiomanicus (Malaysian wood rat), and Sundamys muelleri (Mullers Rat). The most widely caught is Rattus tiomanicus by 15 individuals and captured on all three locations. These indicated that Rattus tiomanicus species have a wide regional spread and range of foods. The highest diversity was Station II (the bush) with Diversity Index Hâ=1.2252, and followed by Station III (riparian areas) and Station I (farm plantation) with diversity indexs Hâ=1.0579 and Hâ=0.9503, respectively.Â